T-Fuzzy Submodules of RxM - Rasul Rasuli (Journal of New Theory)
In this paper, we introduce the concept of T-fuzzy submodule of RxM and give new results on this subject. Next we study the concept of the extension of T-fuzzy submodule of RxM and prove some results on these. Also we investigate T-fuzzy submodule of RxM under homomorphisms or R-modules.